Sex differences in the interrelations between stress, craving and alcohol consumption across individuals and time during baclofen treatment for alcohol dependence. (January 2023) - Logge, Warren; Baillie, Andrew; Haber, Paul; Towers, Ellen; Riordan, Benjamin C.; Morley, Kirsten
Highlights: Potential sex-specific differences have been seen in baclofen treatment for AUD. Drinking, craving and stress interrelationships during baclofen treatment assessed. Autoregressive, multilevel, multivariate network approach assessed sex differences. Baclofen abolishes relationships between stress and drinking in females only. Novel network approach can help elucidating pharmacotherapy mechanism of action. Abstract: Aims: Recent studies have suggested that females respond more favourably to baclofen treatment for alcohol use disorder. Females are generally more likely to drink to regulate stress reactivity and negative affect. This study thus aimed to evaluate the role of sex on the effect of baclofen on the relationship between daily alcohol consumption, stress and craving. Methods: A network analysis of fluctuations using vectorized autoregressive modelling was used to explore the relationship between daily surveys of alcohol consumption, stress and craving from daily diary data over 84 days from a randomised controlled trial of baclofen (30 mg or 75 mg per day) versus placebo in 104 participants with alcohol dependence ( 1, 2 ). Symptom interrelations across patients and across time were examined including temporal networks (time lagged), contemporaneous and between-subjects networks, and were examined for placebo and baclofen stratified by sex. Results: Overall, between persons, there was a significant relationship between stress and drinking in placebo treated individuals in females (r = −0.70, p < 0.001) but not males (r = 0.32, p = 0.054) that was not observed in baclofen treated individuals. No relationship was observed between stress and drinking in the baclofen group for either sex (p's < 0.45). Discussion: There appears to be some sex-specific differences whereby baclofen abolishes an overall association between stress and drinking in females, but this is not observed in males. Network analyses may assist in elucidating the mechanism of action of alcohol pharmacotherapies such as baclofen and understanding which symptoms and mechanisms are key for effective interventions.